Are Rushed Privatizations Substandard? Analyzing Firm-Level Privatization under Fiscal Pressure - Jan Hagemeier; Jan Svejnar; Joanna Tyrowicz (Institute of Labor Economics (IZA), 2018)
In this paper we provide the first analysis of whether rushed privatizations, usually carried out under fiscal duress, increase or decrease firms' efficiency, scale of operation (size) and employment. Using a large panel of firm-level data from Poland over 1995-2015, we show that rushed privatization has negative efficiency, scale and employment effects relative to non-rush privatization. The negative effect of rushed privatization on the scale of operations and employment is even stronger than its negative effect on efficiency. Our results suggest that when policy makers resort to rushed privatization, they ought to weigh these negative effects against other expected effects (e.g. on fiscal revenue).
Keywords: P45; P52; C14; O16; 330; privatization; rushed privatization; efficiency; firm size; employment; performance